Students’ characteristic contribution on personal boundaries in preventing the risk of sexual violence in faith-based boarding schools - Ahmad Yamin; Suryani Suryani; Situ Yuyun Rahayu Fitri; Meita Dhamayanti; Udin Rosidin (Faculty of Nursing Universitas Padjadjaran, 2026)
Background: Personal boundaries are important for establishing students’ identity and defense mechanisms. Strong boundaries help students to recognize limits for interaction, while weak boundaries increase vulnerability for manipulation and sexual violence. In faith-based boarding schools where interactions are intensive, personal boundaries are crucial for preventing harassment. Purpose: This study examines students’ personal boundaries and the determining factors. Methods: A quantitative cross-sectional design applied to 532 respondents recruited through proportionate random sampling from three Faith-Based Boarding Schools (secondary schools) in West Java. Data were collected using a set of questionnaires and were analyzed using the Chi-Square test and logistic regression. Results: More than half respondent (52%) reported weak personal boundaries and among the identified characteristics only students’ age (older) and gender (male) that identified significantly associated with strong personal boundaries (p-value < 0.05). Logistic regression identifies age as the most dominant factor, with each one-unit increase in age increasing the likelihood of personal boundaries by approximately 2.380 times. Conclusions: More than half students have weak personal boundaries. Older and male students tend to have stronger boundaries. There is a critical need for greater awareness and education on personal rights and boundary-setting within these environments, particularly for new (younger) and female students.